Dependency of air curtain performance on discharge air velocity (grille and back panel) in open refrigerated display cabinets - Gaspar, Pedro Dinis (2009)
This study performs a Computational Fluid Dynamics (CFD) modeling of air flow and heat transfer of an open refrigerated display cabinet in order to evaluate the influence of the discharge air velocity on the performance of its recirculated air curtain. The physical-mathematical model considers the flow through the internal ducts, across the fans and the evaporator, and also the thermal response of food products. The fan boundary condition is modeled in order to vary the air velocity at the discharge grille. The back panel perforation is modeled as a porous medium. The density and dimension of the back panel perforation variation is modeled by the Darcy's law with the Forchheimer extension, varying the viscous and inertial resistance coefficients of the porous medium, based on its porosity, permeability, air velocity and pressure loss coefficient. Experimental tests were conducted to characterize the phenomena near the physical borders and to prescribe boundary conditions as well as to validate the numerical predictions on the temperature, relative humidity and velocity distributions.